Oral Peer Feedback in EFL Speaking Classrooms: Exploring Its Implementation and Perceived Influence on Students’ Speaking Confidence and Anxiety - Poppy Fauziah Syafitri; Yuli Tiarina (AL-ISHLAH: Jurnal Pendidikan, 2025)
Speaking is widely recognized as one of the most challenging skills for English as a Foreign Language (EFL) learners due to affective factors such as speaking anxiety, fear of negative evaluation, and low self-confidence. Oral peer feedback has been proposed as a pedagogical approach to address these challenges by fostering learner interaction and reflection. This study employed a descriptive qualitative design to explore the implementation of oral peer feedback and students’ perceived influence of this practice on speaking performance, confidence, and anxiety. The study was conducted at a boarding school, Pondok Pesantren BUMI BOS, involving 38 eighth- and ninth-grade EFL students. Data were collected through classroom observations using an observation checklist and semi-structured interviews with selected students. Data analysis followed the Miles and Huberman framework, including data reduction, data display, and conclusion drawing, with triangulation applied to enhance credibility. The findings showed that oral peer feedback was implemented in a generally supportive and structured manner, characterized by recognition of strengths, balanced positive and constructive comments, and respectful communication. Students perceived oral peer feedback as helpful in increasing awareness of their speaking strengths and weaknesses, enhancing motivation, and building speaking confidence. However, students experienced difficulty providing actionable suggestions, often requiring teacher scaffolding. While many students reported reduced speaking anxiety, some continued to feel nervous when feedback was perceived as overly critical. Ninth-grade students demonstrated higher engagement and confidence than eighth-grade students. The study suggests that oral peer feedback has a positive perceived influence on students’ speaking engagement and confidence, particularly when supported by clear guidelines and teacher guidance, highlighting the importance of structured peer feedback training in EFL speaking classrooms.